Корозійна тривкість сталі 08Х18Н10 із композиційними оксидними покриттями - Штефан, Вікторія Володимирівна; Кануннікова, Надія Олександрівна; Смирнов, Олександр Олександрович; Шепіль, Тетяна Енверівна (Фізико-механічний інститут ім. Г. В. Карпенка НАН України, 2020)
Obtaining materials with high corrosion properties is one of the priorities of the modern world. The modification of the oxide coatings of the steel surface will significantly reduce material costs for repair and downtime. The purpose of this work is the electrochemical study of the resistance of stainless steel with Cr·CrOx; Cr·CrOx·TiOy; Cr·CrOx·AlxOy in chloride medium. The corrosion resistance of composite oxide coatings on steel in a solution of 3,5% NaCl was determined by an electrochemical method, which consisted in the measurement of the free corrosion potentials, the potentiodynamic polarization of the samples, followed by the determination of the pitting potential and the calculation of the pitting resistance. Direct polarization of the working electrode was carried out at a velocity sweep of the potential of 1 mV / s to a value of current density jmax = 1,5 mA / cm2, then the scan was reversed to fully determine the electrochemical parameters of the resistance. Studies on the surface morphology of the samples after polarization were performed using a ZEISSAxio metallographic microscope. The obtained polarization dependences of the forward and backward motion allowed us to determine the potentials of pitting, the potentials of repassation. Calculated bases of pitting resistance ΔEb, ΔErp indicate that oxidized steel has good protective properties in chloride environment. It is revealed that on the surface of AISI 304 steel there are pits and results of fracture at grain boundaries after polarization by surface micrograph. Obtaining composite oxide coatings prevents the formation of pits on materials, which also confirm the obtained electrochemical parameters of pitting.
Corrosion resistance of AISI 304 steel from compositional oxide coatings
Keywords: корозійне руйнування; титан; алюміній; нержавіюча сталь; stainless steel; corrosion; aluminum; titanium; polarization resistance